Increased Loading Rates During Gait Correlate With Morphology of Unaffected Hip in Juveniles With Treated Developmental Hip Dysplasia - Lee, Wei-Chun; Chen, Tsan-Yang; Hung, Li-Wei; Wang, Ting-Ming; Chang, Chia-Hsieh; Lu, Tung-Wu (Frontiers in Bioengineering and Biotechnology, 2021)
Long-term follow-up studies on children with surgically treated developmental dysplasia of the hip (DDH) have shown that not only the affected side progresses to premature osteoarthritis, but the unaffected side may also suffer from insidious hip dysplasia or osteonecrosis. The current gait analysis study identified the loading and unloading rates of the ground reaction forces (GRF) and lower limb joint axial forces during gait, and their correlations with the hip morphology in twenty juvenile patients with surgically treated unilateral DDH during toddlerhood. In a gait laboratory, each subject walked at preferred a speed on a 10-m walkway while the kinematics and the GRF were measured. Loading and unloading rates of the vertical GRF and the joint axial forces were obtained as the maximum instantaneous slope of these force curves. Radiographic measurements of the hips were taken, and the correlations between the morphological parameters and the loading and unloading rates were obtained. The patients showed greater-than-normal peak loading rates of the joint axial forces, and the loading rates on both the affected and unaffected sides were strongly correlated to the acetabular index on the unaffected side, which was also significantly correlated with the peak unloading rates on the affected side. These results suggest that apart from regular follow-up of the affected hip, routine assessment of the morphological changes and/or increased loading rates on the unaffected hip is also important for early identification of any signs of insidious hip dysplasia and risk of premature degeneration of the cartilage.